Análise crítica dos processos de intervenção psicossocial em comunidades e favelas - Nadir Lara Junior (Universidade do Vale do Rio dos Sinos (UNISINOS), 2011)
This article discusses the differences between the concepts, generally treated like synonyms, of favelas and communities. It analyzes the implications of this difference on psychosocial interventions in communities. In order to do that, it presents a review of the concept of community within the Community Psychology and this idea is discussed based on the Lacanian Theory of Four Discourses. The aim is to critically analyze the professionals acting in communities and favelas and how they accept certain concepts naively, maintaining logic of domination in capitalist society. We propose that the frequency of the subjects involved in social work to the discursive field of politics guarantees to those a serious commitment to the logic of desire.